Achieving better service delivery through decentralization in Ethiopia - Garcia, Marito , 1951-; Rajkumar, Andrew Sunil (Africa human development series, 2008)
Ethiopia has made major strides in improving its human development indicators in the past 15 years, achieving significant increases in the coverage of basic education and health services in a short period of time. Imrovements took place during a period of massive decentralization of fiscal resources, to the regions in 1994 and to woredas in 2002-03. The devolutionof power and resources from the federal and regional governments to woredas appears to have improved the delivery of basic services. Surveys of beneficiaries reveal that they perceive that service coverage and quality have improved